SND1 acts as an anti-apoptotic factor via regulating the expression of lncRNA UCA1 in hepatocellular carcinoma - Cui, Xiaoteng (RNA Biol, 2018)
Multifunctional SND1 (staphylococcal nuclease and tudor domain containing 1) protein is reportedly associated with different types of RNA molecules, including mRNA, miRNA, pre-miRNA, and dsRNA. SND1 has been implicated in a number of biological processes in eukaryotic cells, including cell cycle, DNA damage repair, proliferation, and apoptosis. However, the specific molecular mechanism regarding the anti-apoptotic role of SND1 in mammalian cells remains largely elusive. In this study, the analysis of the online HPA (human protein atlas) and TCGA (the cancer genome atlas) databases showed the significantly high expression of SND1 in liver cancer patients. We found that the downregulation or complete depletion of SND1 enhanced the apoptosis levels of HepG2 and SMMC-7721 cells upon stimulation with 5-Fu (5-fluorouracil), a chemotherapeutic drug for HCC (hepatocellular carcinoma). SND1 affected the 5-Fu-induced apoptosis levels of HCC cells by modulating the expression of UCA1 (urothelial cancer associated 1), which is a lncRNA (long non-coding RNA). Moreover, MYB (MYB proto-oncogene, transcription factor) may be involved in the regulation of SND1 in UCA1 expression. In summary, our study identified SND1 as an anti-apoptotic factor in hepatocellular carcinoma cells via the modulation of lncRNA UCA1, which sheds new light on the relationship between SND1 protein and lncRNA.